A swainsonine survey of North American Astragalus and Oxytropis taxa implicated as locoweeds. (August 2016) - Cook, Daniel; Gardner, Dale R.; Lee, Stephen T.; Pfister, James A.; Stonecipher, Clinton A.; Welsh, Stanley L.
Abstract: Swainsonine, an indolizidine alkaloid with significant physiological activity, is an α-mannosidase and mannosidase II inhibitor that causes lysosomal storage disease and alters glycoprotein processing. Swainsonine is found in a number of plant species worldwide, and causes severe toxicosis in livestock grazing these plants, leading to a chronic wasting disease characterized by weight loss, depression, altered behavior, decreased libido, infertility, and death. Swainsonine has been detected in 19 Astragalus and 2 Oxytropis species in North America by thin layer chromatography, gas chromatography–mass spectrometry, liquid chromatography-mass spectrometry and a jack bean α-mannosidase inhibition assay. In addition, 5 species in North America are presumed to contain swainsonine based upon reports from field cases. Many of these plant species have not been analyzed for swainsonine using modern instrumentation such as gas or liquid chromatography coupled with mass spectrometry. To provide clarification, 22 Astragalus species representing 93 taxa and 4 Oxytropis species representing 18 taxa were screened for swainsonine using both liquid chromatography-mass spectrometry and gas chromatography-mass spectrometry. Swainsonine was detected in 48 Astragalus taxa representing 13 species and 5 Oxytropis taxa representing 4 species. Forty of the fifty-three swainsonine-positive taxa had not been determined to contain swainsonine previously using liquid or gas chromatography coupled with mass spectrometry. The list of swainsonine-containing taxa reported here will serve as a reference for risk assessment and diagnostic purposes. Graphical abstract: Highlights: Locoweeds are Astragalus and Oxytropis species that contain the toxin swainsonine. 22 Astragalus species representing 93 taxa and 4 Oxytropis species representing 18 taxa were screened for swainsonine. Swainsonine was detected in 48 Astragalus taxa representing 13 species and 5 Oxytropis taxa representing 4 species. Herbarium specimens are useful resources for phytochemical studies.